The effect of behavior modification program in early secondary school students with obesity and overweight in schools under the Office of the Basic Education Commission, Saeng Sang District - poldongnok, Gattida (Vajira Nursing Journal, 2024)
The quasi-experimental study of one group, pre-post and follow-up, aimed to compare the mean values ​​of food consumption behavior, exercise and nutritional status of 30 obese and overweight lower secondary school students in schools under the Office of the Basic Education Commission (OBEC), Soeng Sang District, before and after receiving the program and follow-up. The sample group was selected by purposive sampling. The inclusion criteria were: 1) lower secondary school students aged 12-15 years and 2) obese and overweight (+2 S.D. to ≥+3 S.D.). The data collection tools consisted of a questionnaire on personal data, food consumption behavior and physical activity behavior, which were tested for reliability using cronbark’s alpha coefficient of 0.85 and 0.84, respectively. The data were analyzed using paired t-test statistics. The results of the research found that the sample group after receiving the behavior modification program had an average score of food consumption behavior and physical activity. Higher than before the experiment with statistical significance (p<.001) and after joining the behavior modification program, it was found that in the post-experiment and follow-up periods, the nutritional status improved from before the experiment as follows: the nutritional status at the beginning of obesity improved from the original by 33.33 percent, the nutritional status at the obesity level improved from the original by 45.83 percent. The results of this research show that the behavior modification program for early secondary school students who are beginning to be obese commission, resulting in better health behaviors.